Protective effects of sea buckthorn polysaccharide extracts against LPS/d-GalN-induced acute liver failure in mice via suppressing TLR4-NF-κB signaling. (24th December 2015) - Liu, Huan; Zhang, Wei; Dong, Shichao; Song, Liang; Zhao, Shimin; Wu, Chunyan; Wang, Xue; Liu, Fang; Xie, Jiming; Wang, Jinling; Wang, Yuzhen
Abstract: Ethopharmacological relevance: Sea buckthorn ( Hippophae rhamnoides L.) berries have been traditionally used to treat gastric disorders, cardiovascular problems, and liver injuries in oriental medicinal system. This study aimed to explore the protective effects and mechanisms of the polysaccharide extracts of Sea buckthorn (HRP) berries against lipopolysaccharide (LPS) and d-galactosamine hydrochloride (d-GalN)-induced acute liver failure in mice. Materials and methods: HRP was isolated by hot-water extraction and characterized by HPLC and infrared spectrum analysis. The total carbohydrate, uronic acid and protein contents of HRP were measured by a spectrophotometric method. Mice were orally administrated with HRP (50, 100, 200 mg/kg) once daily for 14 consecutive days prior to the challenge with LPS (50 μg/kg) and d-GalN (300 mg/kg). Animals of positive control group were intraperitoneally injected with dexamethasone (10 mg/kg). Mice were sacrificed at 8 h after LPS/d-GalN injection. Results: Pretreatment with HRP significantly inhibited LPS/d-GalN-induced increases in serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels, which were accompanied by alleviated liver injuries and reduced production of tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β). HRP was also found to reduce malondialdehyde (MDA) content and to restore superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) activities. Furthermore, HRP supplementation dose-dependently inhibited the expression of Toll-like receptor 4 (TLR4), phosphorylated extracellular signal-regulated kinase (p-ERK), phosphorylated c-Jun N-terminal kinase (p-JNK), and phosphorylated mitogen activated protein kinase 38 (p–p38 MAPK) in the liver of LPS/d-GalN challenged mice. Pretreatment with HRP also inhibited LPS/d-GalN-induced activation and translocation of nuclear factor-κB (NF-κB). Conclusions: This study indicates that pretreatment with HRP protects against LPS/d-GalN-induced liver injury in mice via suppressing the TLR4-NF-κB signaling pathway. Sea buckthorn may be a hopeful drug for prevention of acute live injury. Graphical abstract: